Economic Loss, Strategic Gain: The Geoeconomic Logic Behind China’s Investment in the Jakarta–Bandung High-Speed Rail Project (JBHSR) in Indonesia - Dina Anjelina (LPPM Institut Pendidikan Nusantara Global, 2026)
The Jakarta-Bandung High-Speed Railway (JBHSR) project, established by Indonesia and China is often perceived as an economic failure. The JBHSR project was initiated in 2015 as a pure business-to-business (B2B) project and was scheduled for completion in 2023. A series of problems have occurred in this project, such as construction delays, cost overruns, and low financial feasibility. Despite this, China continues the JBHSR project, which contradicts conventional economic logic, where investors choose to stop due to losses. China’s commitment sparks curiosity, leading to a question as the object of the author's analysis: why does China continue to invest in Indonesia in the Jakarta-Bandung High-Speed Rail (JBHSR) project, even though the project is experiencing short-term financial losses? The author uses a geoeconomic approach by identifying China's actions in converting financial risks in the JBHSR project into strategic leverage for the purpose of sphere of influence, particularly in the Southeast Asian region. This research uses explanatory qualitative methods and data collection techniques based on literature studies. The research indicates that the economic challenges in the JBHSR project did not stop China's involvement, but instead strengthened the structural ties between Indonesia and China through the restructuring of financing from Indonesian loans and technology transfer. The JBSHR represents an economic loss-strategic gain paradox, meaning losses are not a barrier as long as the project successfully delivers significant geopolitical and geoeconomic benefits.